Peran Dan Fungsi Pemerintahan Good Governance Dalam Mendorong Pertumbuhan Ekonomi Di Provinsi Bali - I Gde Surya Kurniawan (Jurnal Ilmiah Cakrawarti, 2020)
Bali in its development cannot be separated from principles that are firmly held by society such as the Tri Hita Karana concept - the human-human relationship,  the human-nature relationship and the human-God relationship. Therefore, including   all components of Balinese society (inclusive growth) in spurring economic growth is a must. The economic growth that occurs must be spread throughout all districts / cities in Bali, especially areas with high poverty rates as an effort to reduce the level of disparity between regions (districts / cities), considering that so far the Balinese economy still relies on the tertiary economy (services sector), and there are The development trend is more concentrated in the southern part of Bali, including Denpasar, Badung, Gianyar and Tabanan (Sarbagita).Based on the research results, it can be concluded that, among others: The im- plementation of good governance in Bali Province is getting better, as indicated by the achievement of LAKIP and LKPD scores for Bali Province, regencies / cities in Bali which are increasing from year to year. This has affected the economic conditions in Bali Province from year to year, which has experienced good development, this can be ob- served in the components of higher economic growth, the number of poor people and the decreasing level of inequality. The implementation of good governance in the Regency Government in the Province of Bali has a very important role in the process of increasing economic growth which leads to the welfare of the community.A number of suggestions that can be conveyed in relation to the discussions that have been submitted are as follows: That good governance is needed to support the im- plementation of government policies that are oriented towards increasing indicators of economic growth and community welfare so that they are more effective and can have a comprehensive impact according to their respective objectives. respectively. The Provin- cial Government as the representative of the central government in the regions can pro- vide a stimulus to Regency / City governments that have implemented good governance in the implementation of good governance, so that it is expected to further encourage   an increase in economic growth and community welfare. Local governments in the Bali Province can further increase their innovation in implementing good governance in the implementation of their main duties and functions.